Beyond Wavering: Post-Colonial Resistance and Norm Contestation in ASEAN’s Response to Myanmar’s Coup - Muhammad, Andra Khagum; Oktaviani, Jusmalia; Panorama , Anggun Dwi (Nation State: Journal of International Studies, 2025)
This study aims to analyze ASEAN's response to the military coup in Myanmar as a form of post-colonial resistance that affects regional norm formation. This study is important because it reveals how collective memories of colonialism shape ASEAN's attitudes towards the concepts of democracy, sovereignty, and intervention, giving rise to the dynamics of norm contestation between the principle of non-intervention and the pressure to protect human rights. The method employed is Critical Discourse Analysis (CDA), which is used to explore the discourse construction and ideology underlying ASEAN policies. The theoretical framework adopted includes norm contestation theory which emphasizes that international norms are dynamic and contested, as well as Dipesh Chakrabarty's post-colonial approach, which highlights historical trauma as the foundation of institutional resistance. The results show that ASEAN's cautious stance is not a weakness, but a form of protection of sovereignty and political identity shaped by colonial experiences. This study contributes to the understanding of the interaction between global and local norms in the post-colonial world, enriching the discourse of international relations from the perspective of the Global South.